Correlations between extent of X-ray infiltration and levels of serum C-reactive protein in adult non-severe community-acquired pneumonia. Issue 6 (June 2015) - Tamayose, Maki; Fujita, Jiro; Parrott, Gretchen; Miyagi, Kazuya; Maeshiro, Tatsuji; Hirata, Tetsuo; Higa, Futoshi; Tateyama, Masao; Watanabe, Akira; Aoki, Nobuki; Niki, Yoshihito; Kadota, Jun-ichi; et al.
Abstract: Pneumonia cases can vary in both severity and chest X-ray findings. Elevated C-reactive protein (CRP) levels may be an indicator of disease severity. We retrospectively evaluated factors correlated with the extent of chest X-ray infiltration both in community-acquired pneumonia (CAP) and a subgroup of cases with pneumococcal pneumonia. In a clinical study that evaluated the efficacy of sitafloxacin, 137 patients with CAP had been previously enrolled. In our study, 75 patients with pneumococcal pneumonia were identified among these 137 CAP patients. The extent of chest X-ray infiltration was scored and correlations with age, sex, body temperature, white blood cell (WBC) count, and CRP levels were analyzed using multivariate analysis with logistic regression. Significant correlations were observed between the extent of chest X-ray infiltration and CRP levels in both CAP and pneumococcal pneumonia. Our data indicates that CRP is a valuable and informative resource that could reflect the severity of pneumonia in cases of both CAP and pneumococcal pneumonia.